Platform as new "daddy": China's gendered wanghong economy and patriarchal platforms behind - Xiaofei Han (Internet Policy Review, 2022)
Wanghong refers to a particular stream of vocational Chinese internet celebrities that have acquired their celebrity online and have acute incentives through various models to liquidate such online influence. While the wanghong economy is often projected as a new platform economy that is by the women and for the women on diverse media outlets in China, this paper highlights the structurally embedded gender hierarchy of the business ecosystem of the wanghong economy and the platform power increasingly associated with patriarchal order. This phenomenon is further exemplified by the updated meanings constructed around the Chinese term "baba" (daddy), which is extensively used by wanghong and netizens to refer to platforms, especially Douyin (Dou Baba), one of the most popular social media platforms in China. By combining the analysis of female participation at different dimensions of the wanghong economy with the "platform-as-daddy" discourses, this paper seeks to connect the industrial analysis of the wanghong economy as one of the most prominent "platform economies" in contemporary China with its cultural dimensions. It accentuates the key roles of major Chinese platform companies as not only new critical intermediaries in perpetuating the ongoing patriarchal system between the state and users but also active participants that construct, and aggressively profit from, the gendered wanghong economy value chains. Analysis of the "platform-as-daddy" discourse also suggests that wanghong and the broader internet users are aware of the asymmetric power dynamics between themselves and the popular platforms. Yet the "platform-as-daddy" narrative, which is jointly built by wanghong and users, further legitimises and even glorifies platform's dominance.
Keywords: 300; Consumers; China; Digital consumption; Digital platforms; gender